White Media Attitudes in the Trump Era. Issue 2 (March 2021) - Thompson, Jack
Scholars and political commentators point to Trump's war on the media since the 2016 election as an unprecedented attack on a vital check to Presidential power. However, little attention has been paid to the role that White audiences play in this critical debate. In this article, I examine the relationship between Trump, the media, and White audiences. Using data taken from the American Trends Panel, I show that affect for Trump is conditional on Whites' selective partisan exposure to conservative news media. My analysis also shows that exposure to political and election news directly from Trump intensifies the relationship between Whites' perceptions of media bias and their distrust of national news organizations. The findings provide a novel and unique contribution to the existing scholarship by demonstrating the causal effect of selective exposure to conservative media outlets on affect for Trump.